2003
DOI: 10.1088/0268-1242/19/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Optimum design on the performance parameters of a two-stage combined semiconductor thermoelectric heat pump

Abstract: A new cycle model of a two-stage combined semiconductor thermoelectric device that is used as a heat pump is established. The influence of Joule heating due to the electric current and heat leak due to the temperature difference between the hot and the cold junctions on the performance of the system is investigated. The general expressions of three important performance parameters, the coefficient of performance (COP), the rate of heat pumping and the power input, are derived. The maximum COP and the correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…The THP does not have moving parts, such as the refrigerant and compressor used in the conventional heat pump. Some studies have been conducted to adapt the THP to a building air conditioning system [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The THP does not have moving parts, such as the refrigerant and compressor used in the conventional heat pump. Some studies have been conducted to adapt the THP to a building air conditioning system [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Lai et al [22] established a new cycle model of a two-stage combined THP system. They suggested that two-stage THP systems have to be used over a large temperature range of the heated space and heat sink.…”
Section: Introductionmentioning
confidence: 99%
“…In those configurations, heat is removed from the cold side of the colder stage, and this heat is continuously transferred to the hot side of the hotter stages. Two param-eters, the maximum cooling capacity and the maximum coefficient of performance (COP), are of particular interest in characterizing TECs (3) . Xuan et al (2) - (5) and Chen et al (3), (6) investigated the maximum temperature difference, the maximum cooling capacity and the maximum COP of two-stage TECs.…”
Section: Introductionmentioning
confidence: 99%
“…Two param-eters, the maximum cooling capacity and the maximum coefficient of performance (COP), are of particular interest in characterizing TECs (3) . Xuan et al (2) - (5) and Chen et al (3), (6) investigated the maximum temperature difference, the maximum cooling capacity and the maximum COP of two-stage TECs. Based on the configurations of two-stage TECs, these works employed derivative methods that involved complicated procedures for optimizing the parameters of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation